Concurrent Conceptual Design and Materials Selection of Natural Fiber Composite Products - Mansor, Muhd Ridzuan (SpringerBriefs in Materials,, 2018)
This book covers topics related to developing natural-fiber composite products during the conceptual design stage in the product development process. It describes the concurrent engineering methods and tools applied in natural-fiber composite product development and discusses the major conceptual design activities, such as geometrical conceptual design development and selection, materials selection and manufacturing process selection. The book also includes case studies with illustrations on the related conceptual design aspects of developing natural-fiber composite products to provide designers with practical guidance on applying the selected tool for their project.